Analisis Sektor-Sektor Potensial Dalam Menentukan Prioritas Pembangunan di Kabupaten Badung Tahun 2001-2011 - Putra, Putu Gede Bayu Nugraha; Kartika, I Nengah (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2013)
This study aims to determine which sector has the potential to be developed as well as the right to determine development priorities in Badung. Methods of data collection in this study through the method of data collection is done through direct observation and documentation method store cord, document, or some literature related to there search. This study uses secondary datain the form of time series of annual data eleven years from 2001-2011, using three analysis namely Location Quotien (LQ), Growth Ratio Model (MRP), and overlay analysis. Of this study showed that the dominant sector in the Badung regency is electricity, gas and water, construction, trade, hotels, and restaurants, and transport and communications sectors.
Keywords: Potential; priorities; Featured